2019
DOI: 10.1097/ijg.0000000000001319
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Deep Learning System For Identifying Glaucomatous Optic Neuropathy Based on Color Fundus Photographs

Abstract: Precis: Pegasus outperformed 5 of the 6 ophthalmologists in terms of diagnostic performance, and there was no statistically significant difference between the deep learning system and the “best case” consensus between the ophthalmologists. The agreement between Pegasus and gold standard was 0.715, whereas the highest ophthalmologist agreement with the gold standard was 0.613. Furthermore, the high sensitivity of Pegasus makes it a valuable tool for screening patients with glaucomatous optic neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 14 publications
0
43
0
1
Order By: Relevance
“…These results are particularly encouraging as any screening program for glaucoma will need to demonstrate a fairly high specificity to minimize the rate of false positive referrals while ensuring that those with functional vision loss are detected. Thus, these and other studies 25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] have demonstrated that there is a viable potential for medical systems to harness existing teleretinal or other telehealth infrastructure for glaucoma screening if the review of such imaging becomes feasibly automated through DL in the future. Three convolutional layers, one max-pooling layer, and one full connection layer.…”
Section: Deep Learning In Color Fundus Photographsmentioning
confidence: 98%
See 4 more Smart Citations
“…These results are particularly encouraging as any screening program for glaucoma will need to demonstrate a fairly high specificity to minimize the rate of false positive referrals while ensuring that those with functional vision loss are detected. Thus, these and other studies 25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] have demonstrated that there is a viable potential for medical systems to harness existing teleretinal or other telehealth infrastructure for glaucoma screening if the review of such imaging becomes feasibly automated through DL in the future. Three convolutional layers, one max-pooling layer, and one full connection layer.…”
Section: Deep Learning In Color Fundus Photographsmentioning
confidence: 98%
“…A majority of the studies included in this review utilized CFPs for training and testing the DL algorithm for the diagnosis of glaucoma. 25,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] The details of each study with CFPs is summarized in Table 1. Fundus photography has already been successfully incorporated into teleophthalmology programs to detect other eye diseases, such as diabetic retinopathy.…”
Section: Deep Learning In Color Fundus Photographsmentioning
confidence: 99%
See 3 more Smart Citations